Secure data communication using blind source separation - Kumar, Anil; Elkhazmi, E. A.; Khalifa, Othman Omran; Albagul, Abdulgani (2008)
In this paper, we presents a secure(noise-resistant algorithm for data communication over the noisy channel , the message is converted to non-linear Hadamard code, which is having the maximum hamming distance, which makes it more fault-tolerant in comparison to the ASCII input. The translated message is encrypted with a random signal by specific mixing. The encrypted message is further permutated and inserted in the image using pseudo-random sequence, which make the system more secure. Experimental results show that this system is working well in noisy environment.